Hypervalent-iodine(iii) oxidation of hydrazones to diazo compounds and one-pot nickel(ii)-catalyzed cyclopropanation. (24th November 2015) - Liu, Haixuan; Wei, Yunyang; Cai, Chun
Abstract : A novel and efficient cyclopropanation protocol that can be applicable to general hydrazones and alkenes with broad functionalities. Abstract : A one-pot process for the catalytic cyclopropanation of various alkenes with unsubstituted hydrazones is described. Iodosobenzene (PhIO) was found to be a competent oxidant of hydrazones to diazo compounds. Ni(OH)2 was chosen as an effective and cheap metal catalyst. The cyclopropane products can be generated efficiently (5 min–4 h) in moderate to good yields (42–91%) under mild (80 °C) and neat conditions.